Unbalance Response of a Hydrogen Fuel Cell Vehicle Air Compressor Rotor Supported by Gas Foil Bearings: Experimental Study and Analysis - Ming Ying; Xinghua Liu (Lubricants)
In rotating machinery, unbalanced mass is one of the most common causes of system vibration. This paper presents an experimental investigation of the unbalance response of a gas foil bearing-rotor system, based on a 30 kW-rated commercial hydrogen fuel cell vehicle air compressor. The study examines the response of the system to varying unbalanced masses at different rotational speeds. Experimental results show that, after adding unbalanced mass, subsynchronous vibration of the rotor is relatively slight, while synchronous vibration is the main source of vibration; when unbalanced mass is added to one side of the rotor, the synchronous vibration on that side initially decreases and then increases with speed, while synchronous vibration on the opposite side continuously increases with speed; when unbalanced mass is added to both sides, the synchronous vibration on each side increases with the phase difference of the unbalanced mass at low speed, while the opposite trend occurs at high speed. The analysis of the gas foil bearing-rotor system dynamics model established based on the dynamic coefficient of the bearing shows that the bending of the rotor offsets the displacement caused by the unbalanced mass, which is the primary reason for the nonlinear behavior of the synchronous vibration of the rotor. These findings contribute to an improved understanding of GFB-rotor interactions under unbalanced conditions and provide practical guidance for optimizing dynamic balancing strategies in hydrogen fuel cell vehicle compressors.